Comparison of a new bioelectrical impedance device and its use in the assessment of body composition - Elvira, C.; Tomás-Casamian, D.; Gomis-Gomis, M. J.; Wyche, L.; Terol-Sanchis, M.; Pérez-Suárez, P. (Scientific Journal of Sport and Performance, 2022)
The objective of the present study is to determine the reliability of the measurements in the parameters of body composition of the Smart Performance measurement device and to compare the results with those produced by the InBody 270 device. Ten professional-level male athletes (mean weight = 58.4 kg ; height = 165.4 cm; BMI = 26.9 kg/m2) were analysed. An experimental design of a single cohort was carried out. Participants were tested on two 5-point bioimpedance devices: In-Body 270 (Biospace, Seoul, Korea) and Smart Performance. Measurements were made in the after-noon (6:30 p.m. - 7:30 p.m.). The variables used were weight (kg), fat mass (kg), muscle mass (kg), body water (L), BMI (kg/m2), protein and minerals. the Smart Performance Composition device presents a high degree of reliability for the analysis of body composition and its use at a recreation-al, sports and scientific level.